Re-scaling home and world: Singaporean artists in New York City - Teng, Celeste (Tufts Archival Research Center, 2019)
This thesis will examine how artists in diaspora engage with politics and nationalism through ethnographic research and exchange with a community of Singaporean artists and writers in New York City. The Singapore government has historically used state funding and censorship to discipline artistic production and mobilise it towards the promotion of of a monolithic, neoliberal vision of national identity. Singaporean artists and writers who live abroad are cultural workers, and their life histories, practices and works point towards a kind of Singapore done differently.